PENGEMBANGAN USAHA MELALUI PENINGKATAN STRATEGI PEMASARAN PADA UMKM KRUPUK RAMBAK BAWANG TUMBAR - Damayanti, Damayanti; Asrori, Muhammad; Ilhami, Susanti Dwi; Mabruroh, Nisa Atul; Mahiza, Rossa Salsabila Hayya (Fokus ABDIMAS, 2023)
MSMEs Krupuk Rambak Bawang Tumbar has an address in Soditan Village, RT.01/ RW.02, Lasem District, Rembang Regency, Central Java. MSMEs Krupuk Rambak Bawang Tumbar is one of the MSMEs in Rembang engaged in food production. The problems faced by Partners are: 1). Erratic weather makes crackers unable to be dried, 2). The product is not yet known by the wider community, 3). Unattractive packaging, 4). Many consumers do not know their location, 5). Lack of variations in the shape of MSMEs Krupuk Rambak Bawang Tumbar product. The service team carried out several programs including: 1). Making a Google Map, 2). Facebook Account Creation, 3). Sticker Making, 4). Making notes and stamps, 5). Making Directions, and 6). Product marketing with another variant in the form of raw crackers. Through this community service activity, it is hoped that MSMEs will be able to compete, increase sales, income and welfare of MSME owners. Keyword: Business Development, MSMEs and Marketing Strategy